Implementasi Metode Collaborative Filtering By Item Based Approach Untuk Strategi Digital Tourism - Astri, Renita; Zulfahmi, Zulfahmi; Faradika, Faradika; Kamal, Ahmad (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
West Sumatra is one of the cities in Indonesia that has many tourist attractions. Tourist attractions are one of the entertainment for people in Indonesia, especially West Sumatra. Provinces that are rich in natural, cultural and artificial tourism are able to give a comfortable impression to tourists visiting this area. In addition to its tourist attractions, the natives of West Sumatra are also kind and friendly to tourists on vacation. In choosing a tourist spot, there are some tourists who look for tours according to their wishes. However, sometimes they get incomplete information about the tour they want. With the rapid development of technology, a system is needed that can help provide information and recommend tourist attractions to tourists. With this system, it is expected to help provide the information desired by users later. This recommendation system uses the Collaborative Filtering method with an item-based approach. The recommendation process in this system is done by calculating Similarity between specifications that make up an item of tourist attractions that users want with the specifications of tourist attractions contained in the system. This system produces recommendations for tourist attractions with information about tourism in West Sumatra, and can provide solutions for tourists in choosing a place of tourism that suits their desires.